1986
DOI: 10.1159/000153638
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Groups and Lung Cancer

Abstract: Haptoglobin groups were investigated in 309 patients with primary lung cancer divided by sex, smoking habits and tumor type. Patients with squamous epithelial cancer and oat-cell cancer showed no significant difference from normal controls. Among patients with pulmonary adenocarcinoma the frequency of the Hp 2–2 type was significantly (p < 0.05) lower compared to the controls, with a corresponding increase of the Hp 1–1 and Hp 2–1 types. This difference was more pronounced (p < 0.025) among females with pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…In some studies, the Hp2-2 frequency was significantly lower in patients with pulmonary adenocarcinoma and bladder carcinoma than in normal subjects (Beckman et al, 1986;Benkmann et al, 1987), whereas a significantly higher frequency of Hp2-1 and Hp2-2 phenotypes was found in patients with esophageal and gastric cancer (Jayanthi et al, 1989).…”
Section: Cancermentioning
confidence: 95%
“…In some studies, the Hp2-2 frequency was significantly lower in patients with pulmonary adenocarcinoma and bladder carcinoma than in normal subjects (Beckman et al, 1986;Benkmann et al, 1987), whereas a significantly higher frequency of Hp2-1 and Hp2-2 phenotypes was found in patients with esophageal and gastric cancer (Jayanthi et al, 1989).…”
Section: Cancermentioning
confidence: 95%
“…A deficit of group 0 in lung cancer observed in the last study was not supported by the other seven, and various associations of blood groups with certain histological types and with proximal tumours reported by Ashley (1969) were again not present in the other studies. Beckman et al (1986) reported the distribution of haptoglobin groups in lung cancer patients and controls and reviewed three similar studies -an association in their own study was not present in the others. Of five studies that have sought associations between HLA antigens Bodmer (1986) has shown that such associations of two unrelated genes on the same chromosome could have persisted (in the absence of natural selection) only with extremely close linkage, with recombination fraction approaching 0.1%.…”
Section: Familial Clustering Of Lung Cancer Casesmentioning
confidence: 95%
“…11,14) It is produced in the liver and immunological cells and secreted into serum. Its level changes in the serum in response to infection, inflammation, and various malignant diseases, including lung and bladder cancer, 15,16) leukemia, 17) breast cancer, 18) malignant lymphoma, 19) urogenital tumors, 20) and esophageal squamous cell carcinoma. 21) Of these 41 genes, we especially observed Hp gene.…”
Section: Haptoglobin Proved a Prognostic Biomarker In Peripheral Bloomentioning
confidence: 99%